2017
DOI: 10.1055/s-0043-113325
|View full text |Cite
|
Sign up to set email alerts
|

Development of a High-Performance Liquid Chromatographic Method for Asiaticoside Quantification in Different Skin Layers after Topical Application of a Centella asiatica Extract

Abstract: The topical application of extract has been commonly used for many different purposes but especially for cosmetic use in the treatment of gynoid lipodystrophy. Asiaticoside, the most active component in this extract, is responsible for its therapeutic activities. However, little is known to date about asiaticoside skin penetration. Thus, an analytical method for asiaticoside quantification in different skin layers after the topical application of extract was developed and skin permeation studies were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Centella asiatica , a herb of the apiaceae family ( 5 ), contains a variety of active ingredients, such as triterpenoids and saponins ( 6 ). AC and madecassoside are the principal monomer components of saponins in C. asiatica ( 7 ). Previous studies have revealed that AC possesses a wide range of biological functions, such as facilitating angiogenesis by increasing collagen synthesis ( 8 , 9 ), inhibiting inflammatory process ( 10 , 11 ), suppressing scar formation ( 12 , 13 ) and promoting wound healing ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Centella asiatica , a herb of the apiaceae family ( 5 ), contains a variety of active ingredients, such as triterpenoids and saponins ( 6 ). AC and madecassoside are the principal monomer components of saponins in C. asiatica ( 7 ). Previous studies have revealed that AC possesses a wide range of biological functions, such as facilitating angiogenesis by increasing collagen synthesis ( 8 , 9 ), inhibiting inflammatory process ( 10 , 11 ), suppressing scar formation ( 12 , 13 ) and promoting wound healing ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results are within limits and considered acceptable for bioanalytical methods (FDA, 2018). Moreover, considering the analytical challenge, the recovery results achieved by this method are superior to other analytical methods developed for drug quantification in skin published by our research group and by others (Ângelo, Cunha-Filho, Gelfuso, & Gratieri, 2017;da Rocha et al, 2017;Reis et al, 2018).…”
Section: Methods Validationmentioning
confidence: 74%
“…The analysis of quercetin 3- O -β-D-glucuronide (quercetin 3-glucuronide) and asiaticoside was performed with reference to methods previously published ( Schneider et al, 2008 ; Rafamantanana et al, 2009 ; Benmeziane et al, 2016 ; da Rocha et al, 2017 ). Approximately 3.0 mg each of quercetin 3-glucuronide and asiaticoside standard compounds were placed in a 3-mL volumetric flask and dissolved with methanol.…”
Section: Methodsmentioning
confidence: 99%